Chronic or Recurrent Invasive Fungal Sinusitis after COVID-19 Infection - Ghorbani, Jahangir; Raad, Nasim; Karimi Galougahi, Mahboobeh; Dehghani Firouzabadi, Amrollah (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: During the COVID-19 epidemic, we have witnessed numerous manifestations and complications after contracting this disease. One of these complications in patients with COVID-19 is the increased risk of invasive fungal infections due to the suppression of the immune system caused by the disease or due to the use of suppressive drugs such as corticosteroids. Case presentation: Here we report three cases of invasive fungal sinusitis after contracting COVID-19 with recurrence after primary treatment and the measures taken for these patients. Discussion: Invasive fungal sinusitis with involvement of orbit or brain is a known complication in COVID-19 patients especially in diabetics. Recurrence of manifestations of fungal infection after primary treatment and hospital discharge may be related to uncontrolled underlying disease and residual fungal infection especially in necrotic soft tissue or bone. Conclusion: Early diagnosis and management with antifungal drugs and surgical debridement and also close follow up after discharge from hospital is essential for treatment and achieving higher survival in patients with invasive fungal sinusitis.